Towards Sustainable Growth : Examining The Interplay Of Good Governance, Earnings Management, Tax Compliance, And Firm Longevity - Tursinah Anggendari; Sarah Fitriyani (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to investigate the interplay between good governance, earnings management, tax compliance, and firm longevity in fostering sustainable futures for organizations. Employing a qualitative research design, the study utilizes semi-structured interviews with key stakeholders from a diverse range of firms. Sampling techniques involve purposive sampling to ensure representation across industries and organizational sizes. Data analysis adopts thematic analysis, allowing for the identification of patterns and themes within the qualitative data. The findings reveal intricate relationships between governance practices, earnings management strategies, tax compliance behaviors, and long-term firm sustainability. Insights from this study contribute to the understanding of how organizational practices influence sustainability and inform policymakers and practitioners on fostering responsible corporate behavior for long-term viability.